Determinación de la eficiencia en el control de malezas con herbicidas pre emergentes y post emergentes en el cultivo de girasol (Helianthus annuus L.) en la zona de Quevedo. - Sabando Cantos, Ivo Alexander (2018)
The cultivation of sunflower is of economic importance in Ecuador, it is developed in most types of soil, being the most recommended deep soils, with good drainage and a neutral pH or slightly alkaline, within the agronomic management it is necessary to control the weeds either manually or chemically, based on this one of the most economical ways is to select herbicides that do not harm the development of the plant among which can be pre-emergent and post-emergent early herbicides. Based on this, the objective was to establish the effectiveness of the pre-emergent herbicides in the control of weeds in the sunflower crop and to determine the herbicide or early emergent post-action herbicides in the efficient control of narrow leaf weeds in the cultivation of sunflower. The investigation was carried out during the rainy season in the Experimental Farm "La María", km 7 via Quevedo-El Empalme. In the Western longitude of 79 ° 29'52 '' and South latitude of 1 ° 05'18 ", at a height of 75 masl and irregular topography. The design of Random Complete Blocks (BCA) was used, with 8 treatments that included two pre-emergent herbicides named Pedimentalina and Butachlor, and two post-emergent herbicides named Clethodim and Haloxyfop-R, completing the treatments Interactions among them, performed in 3 repetitions. After the interpretation and analysis of the results, the following conclusions were obtained: the application of Pedimentalina as a pre-emergent in combination with the Haloxyfop-R as an emerging post achieved the highest percentage of control at 7, 14 and 21 days after its application in the crop with a percentage of 87.3%, 82.5%, and 79.2% respectively and the combination between Pedimentalin and Haloxyfop-R presented the lowest average percentage of weed regrowth at 30 days after application in the sunflower crop with a percentage of 15.7%. Keywords: Sunflower, Pre-emergent, Post-emergent, weeds